Para‐Selective Arylation of Arenes: A Direct Route to Biaryls by Norbornene Relay Palladation. Issue 47 (9th September 2020) - Dutta, Uttam; Porey, Sandip; Pimparkar, Sandeep; Mandal, Astam; Grover, Jagrit; Koodan, Adithyaraj; Maiti, Debabrata
Abstract: Biaryl compounds are extremely important structural motifs in natural products, biologically active components and pharmaceuticals. Selective synthesis of biaryls by distinguishing the subtle reactivity difference of distal arene C−H bonds are significantly challenging. Herein, we describe para ‐selective C−H arylation, which is acheived by a unique combination of a meta ‐directing group and norbornene as a transient mediator. Upon direct meta ‐C−H palladation, one‐bond relay palladation occurs in presence of norbornene and subsequently para ‐C−H arylation is achieved for sulfonates, phosphonates and phenols bearing 2, 6‐disubstitution patterns. The protocol is amenable to electron‐deficient aryl iodides. Multisubstituted arenes and phenols are obtained by postsynthetic modification of the products. The protocol allows the synthesis of hexa‐substituted benzene by sequential selective distal C−H functionalization. Abstract : The para ‐selective arylation of sulfonate, phosphonate, and phenol derivatives bearing 2, 6‐disubstitution patterns and a suitable meta ‐directing group is achieved by using Pd and norbornene cooperative catalysis. The present protocol enables the synthesis of hexa‐substituted arenes by sequential regioselective C−H functionalization.